THE INFLUENCE OF COMBATIVES ON GENERAL MOTOR PERFORMANCE OF PUPILS (Fiep Bulletin - online, 2014)
The author in his article solves the problem of using preparatory combatives at primary school, especially the influence of preparatory combatives on general motor performance of young children at primary school. The main research method was pedagogical experiment during schools year 2011/2012 at primary schools in Banska Bystrica. At experimental groups boys and girls author used preparatory combatives and fall down techniques during P.E. lessons. The pupils were 10 years old. Before and after pedagogical experiment we realised measurements of general motor performance by tests: shuttle run 4x10 m, 12 minute run, sit-ups 60 s, standing broad jump, bent arm hang and JCMT test. 1st measurement was realised in September 2011 and 2nd measurement in June 2012. The author found out the statistically significant results at experimental groups boys and girls and improvement especially in speed and strength abilities. Combatives together with exercises from athletics, sports games, motor games, gymnastics had positively influence on general motor performance of pupils at primary school. The author is recommending putting preparatory combatives and also fall down techniques to P.E. lessons at primary school.